Science-policy guidelines as a benchmark: making the European Water Framework Directive - Lagace, E; Holmes, J; McDonnell, R (2008)
In recent years, a number of governments have made moves towards evidenced-based policymaking justified by the assertions that scientific understanding makes for better-informed and more effective legislative and regulatory decisions. Some of these governments have produced generic, almost step-by-step recipes, for the use of evidence in policymaking in the form of 'science-policy guidelines'. The usefulness of these somewhat linear procedures has not been assessed in the actual process of policymaking. Using as a benchmark the guidelines developed by the European Commission, this paper examines the collection and use of scientific advice in the development of the European Water Framework Directive. © The Authors. Journal compilation © 2008 Royal Geographical Society (with the Institute of British Geographers).